Ferment In Our Field: Viewing Agricultural Communication Research From a Social Science Perspective - Mark Tucker (Journal of Applied Communications, 1996)
About 10 years ago, The Journal of Communication published a special edition titled "Ferment In the Fleld" in which communication scholars discussed the discipline's history and future in a changing intellectual atmosphere.